Diseño de una maquina separadora y trituradora de paneles de aluminio pre-aislado para la empresa ITC Aire SAS. (2020)
In recent years there has been an increase in environmental pollution due to the excessive consumption of products of polymeric origin, these polymers are mostly thermosetting polymeric elements, which do not allow their reuse once manufactured. Currently in high precision ventilation systems it is necessary to use insulating elements with low heat transfer rates, such as pre-insulated aluminum panels, which consist of two 60 μm embossed aluminum sheets that cover a sheet of polysociunorate foam which is a thermoset polymer. As we said before, pre-insulated aluminum panels are used in the construction of high precision air conditioning and ventilation systems, to be exact in the ducts of the system. These ducts have a manual construction in which the panel is cut into different shapes and sizes to generate different geometries in the system, by generating these geometries part of the initial material is lost as excess material from the generation of the air conditioning ducts, this Material has a high cost of disposal since it is a highly polluting material and is disposed by specific companies to deposit it in areas with special permits, which does not eliminate the main problem in terms of environmental contamination.